A quantitative approach identifies the critical flow characteristics in a natural draft dry cooling tower. (25th February 2018) - Wang, Weiliang; Lv, Junfu; Zhang, Hai; Liu, Qing; Yue, Guangxi; Ni, Weidou
Highlights: A half-cylindrical NDDCT CFD model is built and validated by a hot state test rig. FLF is derived and verified to quantitatively describe flow characteristics effect. Rear side flow separation area and main stream vortices are critical to ventilation. The contributions of each flow field region on ventilation degradation is exhibited. Flow convergence are transformed to be vortices barrier under high crosswind. Abstract: The natural draft dry cooling tower (NDDCT) is a critical facility for an indirect dry cooling power plant in arid area for its merit of excellent water-saving. While crosswind degrades the performance of a NDDCT by changing the flow field inside and outside. In order to quantitatively study the influence of different flow characteristics on the performance of a NDDCT, hence to grasp the affecting mechanism of crosswind, a half-cylindrical computational fluid dynamics (CFD) model of a Heller type 660 MW NDDCT is developed and validated by a hot state modelling test rig. A flow loss factor (FLF) is derived and verified to linearly describe the effect of local flow field changing on the overall performance of a NDDCT. Based on the conjoint studies of the local FLF variation trends and the changing processes of correspondent flow characteristics in each specific flow segments, the critical factors influencing the performance of a NDDCT are identified under different crosswind conditions.